The Role of Job Insecurity, Perceptions of Organizational Support and Organizational Commitment to Employees’ OCB - Kristyowati, Natalia Devi; Widhiastuti, Hardani (Munazzama: Journal of Islamic Management and Pilgrimage, 2022)
This study aims to analyze the effect of job insecurity, Perceived Organizational Support (POS),and organizational commitment on organizational citizenship behavior (OCB). The number ofsamples in this study was 73 respondents. The validity test used the Product Momentcorrelation, while the reliability test used the Alpha formula technique. The prerequisite testscarried out were the normality test using the Kolmogorov Smirnov test, and themulticollinearity test using the tolerance value and the variance inflation factor (VIF).Meanwhile, a test of dastisity used a scatterplot graph. Hypothesis testing used pathanalysis, while sobel test was to test the strength of the indirect effect of the independentvariable on the dependent variable through mediating variable. The analysis showed that jobinsecurity had an effect of 0.446 and perceived organizational support (POS) had an effect of0.454 on organizational citizenship behavior (OCB). Organizational commitment was proven tobe able to mediate the effect of perceived organizational support (pos) on organizationalcitizenship behavior (OCB) with a z value of 3.255. Meanwhile, organizational commitmentproved unable to mediate the effect of job insecurity on organizational citizenship behavior(OCB).